Ichthyosis vulgaris: An updated review - Huda Jaffar; Zobia Shakir; Gaurav Kumar; Iman Fatima Ali (Wiley, 2023)
Abstract Ichthyosis vulgaris is an inherited, non‐syndromic form of ichthyosis that presents with skin problems. Making up more than 95% cases of ichthyosis, ichthyosis vulgaris is caused by heterozygous loss‐of‐function mutation of the filaggrin gene, raising the fragility and permeability of the stratum corneum. It typically presents in infancy as xerosis, skin lesions, keratosis pilaris, palmoplantar hyper linearity, scaly dermatosis, and erythroderma, clearly identifiable by age 5. Although majority of patients have a normal lifespan, possible complications include a vitamin D deficiency and auditory problems due to scaling in the ears, besides a drop in quality of life due to dermatological changes. Urea‐based creams with 10% urea, ceramides, and other ceramides are often the first line therapy in ichthyosis vulgaris. There is no known curative treatment for ichthyosis vulgaris, but lifelong treatment can alleviate the symptoms. Urea‐based creams are highly therapeutic, whereas ammonium lactate 12% lotion with a physiological lipid‐based repair cream can help with scaling and dryness. There is also evidence in favour of propylene glycol solutions. Risankizumab, an anti‐interleukin‐23 drug, and enhancement of natural moisturizing factors are also two highly promising solutions that require additional research. This review aims to provide updates on the manifestation, evaluation, and treatment of ichthyosis vulgaris.